The Effect of Capital Structure and Dividend Policy on Firm Value with Corporate Social Responsibility (CSR) as a Moderating Variable (2021–2024) - Salma Husniyah; Sofia Windiarti (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The non-cyclical consumer sector underwent persistent fluctuations in firm value between 2021 and 2024, mainly caused by continuous changes in financial indicators. This research aims to explore how capital structure and dividend policy impact the value of a firm, with Corporate Social Responsibility (CSR) acting as a moderating factor, specifically for non-cyclical consumer firms listed on the Indonesia Stock Exchange (IDX) during the duration of the study. The research sample includes 20 non-cyclical consumer firms that are listed on the IDX. The data were evaluated using Moderated Regression Analysis (MRA) with the support of IBM SPSS Statistics version 27. The findings indicate that capital structure does not significantly influence firm value, while dividend policy has a notable impact on it. Furthermore, capital structure and dividend policy together affect firm value. Nonetheless, CSR does not serve as a moderator for the effects of each independent variable separately, although it can moderate the overall connection between capital structure, dividend policy, and firm value.